Gastric cancer in autoimmune gastritis: A case‐control study from the German centers of the staR project on gastric cancer research. Issue 2 (1st March 2020) - Weise, Friederike; Vieth, Michael; Reinhold, Dirk; Haybaeck, Johannes; Goni, Elisabetta; Lippert, Hans; Ridwelski, Karsten; Lingohr, Philipp; Schildberg, Claus; Vassos, Nikolaos; Kruschewski, Martin; Krasniuk, Iurii; et al.
Abstract : Objectives: Patients with autoimmune gastritis (AIG) are reported to have an increased risk of developing gastric cancer (GC). In this study, we assess the characteristics and outcomes of GC patients with AIG in a multicenter case‐control study. Methods: Between April 2013 and May 2017, patients with GC, including cancers of the esophagogastric junction (EGJ) Siewert type II and III, were recruited. Patients with histological characteristics of AIG were identified and matched in a 1:2 fashion for age and gender to GC patients with no AIG. Presenting symptoms were documented using a self‐administered questionnaire. Results: Histological assessment of gastric mucosa was available for 572/759 GC patients. Overall, 28 (4.9%) of GC patients had AIG (67 ± 9 years, female‐to‐male ratio 1.3:1). In patients with AIG, GC was more likely to be localized in the proximal (i.e. EGJ, fundus, corpus) stomach (odds ratio (OR) 2.7, 95% confidence interval (CI) 1.0–7.1). In GC patients with AIG, pernicious anemia was the leading clinical sign (OR 22.0, 95% CI 2.6–187.2), and the most common indication for esophagogastroduodenoscopy (OR 29.0, 95% CI 7.2–116.4). GC patients with AIG were more likely to present without distant metastases (OR 6.2, 95% CI 1.3–28.8) and to be treated with curative intention (OR 3.0, 95% CI 1.0–9.0). The five‐year survival rates with 95% CI in GC patients with and with no AIG were 84.7% (83.8–85.6) and 53.5% (50.9–56.1), respectively (OR 0.25, 95% CI 0.08–0.75, p = 0.001). Conclusions: Pernicious anemia leads to earlier diagnosis of GC in AIG patients and contributes significantly to a better clinical outcome.